Peningkatan Pemahaman Bahasa, Budaya, Agama Islam Indonesia dalam KKN (Kuliah Kerja Nyata) Internasional di Negara Thailand - Izaz Vito Adyuta; Nabiel Ba Ramadani Ansori; George As’ad Haibatullah El Masnany; Shafiyyah Tamala Yunfa; Shofi Robiatul Izza; Zuhrotun Navisa; Maulidiana Rahmah; Nihalun Nada (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Improving the quality of society with KKN (Real Work Lecture) is a program for students in carrying out the Tridarma of higher education. This research aims to improve the understanding of language, culture and Islamic religion to the Thai people, which in this case is teaching students in schools in the Songkla region, Pattani, Yala, South Thailand. Students participate in teaching language, culture and Islamic religion in the Student Outbont Mobility program to increase understanding for Thai students to get to know about Indonesia. The main goal of this program is for Thai students to get to know and understand about Indonesian language, culture, and Islamic religion which later they will continue to study in Indonesia.